Biochar Effects on Weed Management - Neeta Soni; Ramon G. Leon; John E. Erickson; Jason A. Ferrell (EDIS)
Biochar can potentially provide better conditions in the soil to increase plant growth. However, research has shown that weed species show minimal changes in germination and emergence patterns with the addition of biochar. Regardless, if biochar is used in the field it is important to monitor for changes in weed populations. This is especially important because biochar can decrease herbicide efficacy. This 3-page fact sheet was written by Neeta Soni, Ramon G. Leon, John E. Erickson, and Jason A. Ferrell, and published by the UF Department of Agronomy, March 2015. (Photo: Neeta Soni)